The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1128/jcm.35.4.873-876.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human immunodeficiency virus type 1 (HIV-1) DNA and RNA sequences in HIV-1 antibody-positive blood donors in Uganda by the Roche AMPLICOR assay

Abstract: The ability of commercially available PCR-based assays to accurately detect or quantitate human immunodeficiency virus type 1 (HIV-1) DNA or RNA in individuals predominantly infected with HIV-1 subtypes A and D is not known. Therefore, peripheral leukocytes from 43 individuals in Kampala, Uganda, positive for HIV by the Western blot (immunoblot) assay were tested by using the Roche AMPLICOR HIV-1 assay for the detection of DNA gag sequences. Plasma from these same individuals was tested by using the Roche HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…It was reported that a decrease in amplification efficiency occurs with five to six mutations in the primerbinding region (10,24), and this amount of divergence occurs most frequently with subtypes A and E. Similar results were reported when samples from Uganda, where subtypes A and D predominate, were tested with the Amplicor HIV-1 DNA test; the sensitivity for the samples from Uganda was 74% (22). Replacement of the primer-probe set selected from the gag gene with a primer-probe set from the better conserved pol gene increased the sensitivity of the DNA detection assay to 98% (22). Similarly, Respess et al (35) reported 100% sensitivity for detection of subtypes A and E with pol-based primers but only 87 and 67% sensitivities, respectively, when gag-based primers were used.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It was reported that a decrease in amplification efficiency occurs with five to six mutations in the primerbinding region (10,24), and this amount of divergence occurs most frequently with subtypes A and E. Similar results were reported when samples from Uganda, where subtypes A and D predominate, were tested with the Amplicor HIV-1 DNA test; the sensitivity for the samples from Uganda was 74% (22). Replacement of the primer-probe set selected from the gag gene with a primer-probe set from the better conserved pol gene increased the sensitivity of the DNA detection assay to 98% (22). Similarly, Respess et al (35) reported 100% sensitivity for detection of subtypes A and E with pol-based primers but only 87 and 67% sensitivities, respectively, when gag-based primers were used.…”
Section: Discussionsupporting
confidence: 68%
“…In the multiplex HIV-1/2 qualitative RNA assay described here, these difficulties were overcome by the meticulous choice of primers and cycling conditions, without compromising sensitivity for HIV-1 detection. The multiplex assay for HIV-1 and HIV-2 detection has a sensitivity of 20 to 50 copies per ml for HIV-1, which is similar to the sensitivities of ultrasensitive versions of assays that detect only HIV-1 (22,30,37). Sensitivity is also critical for detection of HIV-2, especially since lower HIV-2 RNA levels in plasma have been demonstrated (29,41).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The πCode assay platform is based on the IntelliPlex1000 πCode Processor, an automated hybridizing and washing machine, and the PlexBio100 Analyzer for the fluorescent signal detection of the πCode MicroDiscs. Despite the high detection sensitivity achieved with the sk145 and skcc1b primer set, further optimization can accomplish a much higher sensitive HIV-1 DNA assay using different sets of primers, considering the limitation of the sk145 and skcc1b primer set to detect non-B clade HIV-1 subtypes [45,[78][79][80]. In future studies, we will use a different primer set that can potentially achieve a successful detection of all HIV-1 subtypes plus maximum sensitivity for HIV-1 DNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating a limited number of RNA transcripts representing sev-eral different clades, the Chiron bDNA assay appeared to quantify the subtypes similarly (22). Modification of the procedures and/or the primers of other assays may improve detection of different clades of HIV-1 by these assays (20). A comprehensive set of reagents representing the various clades will be needed to provide standards for appropriate comparability studies with kits from various manufacturers.…”
Section: Effect Of Assay and Biologic Variation On Detectionmentioning
confidence: 99%